(untitled) (Journal of Global Arts Studies, 2024)
Background: As the main means of transportation in the city, the subway is an indispensable part of people’s daily life. As a living environment, the subway’s indoor space bears the pressure of urban traffic. At the same time, its comfort and visual beauty are increasingly concerned by the public. Objective: Through the design of cultural and creative products in subway stations, we develop cultural and creative products that meet the needs of the public and highlight the characteristics of urban areas. Methods: The basic method of this study is literature analysis. Results: It is particularly important to improve the comfort level of subway space, make full use of the cultural value of subway stations, enhance urban cultural publicity, create a city business card, and promote tourism development. Conclusion: Through the development and production of cultural and creative products, it can bring economic benefits to relevant enterprises and create job opportunities for relevant employees.